(untitled) (Journal of Education and Development, 2019)
The technological revolution of the past two decades has changed communication, higher education, and the global society. As a result, there exists a wide gulf between the unlimited use of technology and higher education, particularly with respect to digital communications between professors and students. Web 2.0 digital technologies convey information in a different manner than before and allow for interaction with distance participants. Personal use of digital technologies for social media communication is one thing; social media use by professors for communication with students is another. Both aspects should be examined in detail to determine the future directions for global learning.